Equivalência de estímulos e ensino de leitura: uma análise da produção nacional da Análise do Comportamento publicada de 1989 a 2007 - Pereira, Tatiana Almendra Garcia (2009)
The theoretical-methodological chain of Behavioural Analysis, among many studies about the teaching of reading, has produced knowledge related to the equivalent stimuli paradigm. In Brazil, one of the first studies, published in 1989, was one from De Rose, Souza and Rositto. There has since been almost 20 years of scientific production and much has been done. In the absence of any systematic organisation of that which has been produced, the present study had, as its objective, the analysis of national scientific production, published in the form of articles between 1989 and 2007; articles, about the employment of the equivalent stimuli paradigm in the teaching of reading. In relation to the definition of the material to be analysed, it was opted for national articles published in national publications and collections of texts in which the gathering of studies and research realised by behavioural analysts was stipulated. Two procedures were employed to collect the material: 1) the researching of the Qualis-Capes portal of national articles and 2) researching via the bibliographical references contained in the material found. As a result, 44 works that dealt with the equivalent stimuli paradigm theme and 22 which dealt directly with the teaching of reading behaviour by means of the equivalent stimuli paradigm were obtained. Initially, the entirety of the works was targeted for general analysis, focusing on the distribution of publications over each five year period, the proposed work objectives and the characteristics of the subjects. Following on from this, as a central focus analysis was directed towards the teaching of reading from the advent of the equivalent stimuli paradigm and was therefore focused on, among other things, the nature of the work, proposed objectives, the characteristics of the subjects, the delineating of the research, the context application, the characteristics of teaching procedures, the obtained results and the gaps indicated by the authors. The results of the present research allow a mapping of the way that until now was being followed by the Brazilian researchers. Not only evidencing the potential of the equivalent stimuli paradigm as a tool for the teaching of reading, but also revealing the gaps which merit investigation, so that it can in fact materialize in the near future